A good night out for the girls : popular feminisms in contemporary theatre and performance - Aston, Elaine ; Harris, Geraldine (Palgrave Macmillan, 2020)
Moving across the boundaries of mainstream and experimental circuits, from the affective pleasures of commercially successful shows such as Calendar Girls and Mamma Mia! to the feminist possibilities of new burlesque and stand-up, this book offers a lucid and accessible account of popular feminisms in contemporary theatre and performance.Introduction: "a good night out for the girls" -- Jam and Jerusalem, sentimentality and feminism: Calendar girls -- Roaring women and class acts: The naked truth and the Chippendales' Ultimate girls night out -- Age liberation: Susan Boyle, "Grumpy old women" and Virginia Ironside's monologues -- Once more with feeling: Joanna Murray-Smith's The female of the species and Nic Green's Trilogy -- Work, family, romance and the utopian sensibilities of the chick megamusical Mamma Mia! -- The ghosts of new burlesque -- Entertaining others: Shappi Khorsandi and Andi Osho -- "Are we there yet?": final reflections and Marisa Carnesky's Ghost train.